2012
DOI: 10.1186/1471-2458-12-893
|View full text |Cite
|
Sign up to set email alerts
|

Health-related and social factors predicting non-reemployment amongst newly unemployed

Abstract: BackgroundMany researchers have examined the effect that mental health has on reemployment opportunities amongst the unemployed, but the results are inconclusive. Our aim in this study is to investigate the effects that different aspects of mental and physical health, as well as socio-demographic, social, and economic factors, have on reemployment.MethodsA questionnaire was administered to 1,000 and answered by 502 newly registered unemployed Swedes, who were followed for one year using data from the Swedish N… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
10
0
2

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 48 publications
1
10
0
2
Order By: Relevance
“…Individuals aged 50–65 years face a double vulnerability: social and physical. Firstly, a lower probability of being reemployed than younger ones [ 30 , 31 ] would make individual job loss a relevant factor leading to very important levels of strain or hardships for affected middle-aged individuals during economically challenging times in a context of generalized job insecurity. The diminished expectations of finding a new job would increase their stress, which might raise the risk of increasing the intake of alcohol.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Individuals aged 50–65 years face a double vulnerability: social and physical. Firstly, a lower probability of being reemployed than younger ones [ 30 , 31 ] would make individual job loss a relevant factor leading to very important levels of strain or hardships for affected middle-aged individuals during economically challenging times in a context of generalized job insecurity. The diminished expectations of finding a new job would increase their stress, which might raise the risk of increasing the intake of alcohol.…”
Section: Discussionmentioning
confidence: 99%
“…Middle-aged and older individuals have greater risk of alcohol-related problems than younger age groups, as they are more vulnerable to the adverse effects of alcohol due to age-related changes [ 26 , 27 ], such as increased sensitivity and decreased tolerance to alcohol and a slower metabolism [ 28 , 29 ]. Economic downturns and shrinking job markets have a substantial negative impact on the re-employment opportunities among individuals approaching retirement [ 30 , 31 ]. This adverse context could place them at higher risk of adopting dangerous drinking patterns.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies including meta-analyses have found support for both mechanisms. On the one hand pre-existing mental ill health is associated with an increased risk of unemployment [2, 58] and a lower likelihood of re-employment [2, 9, 10]. On the other hand unemployment is followed by poorer [13, 6, 11, 12] and re-employment by improved mental health outcomes [1, 2, 9, 12, 13].…”
Section: Introductionmentioning
confidence: 99%
“…2) Entre los inmigrantes, el desempleo se asocia a un mayor consumo para ambos patrones, aunque la fuerza de la asociación es superior en el CEP. La razón mayoritaria para inmigrar suele ser trabajar (Skarlund, Ahs, y Westerling, 2012), y el impacto de su presencia o ausencia parece influir notablemente en el consumo de alcohol en esta población, como ya había sido indicado (So y Wong, 2006). La relación entre deterioro de salud, consumo de alcohol y desempleo es multidireccional.…”
Section: Discussionunclassified
“…La relación entre deterioro de salud, consumo de alcohol y desempleo es multidireccional. Cada uno de estos factores pueden ser causa o consecuencia de los demás (Skarlund et al, 2012). Y si esto ocurre en cualquier población, es especialmente importante en la inmigrante, cuya situación laboral y redes de apoyo suelen ser más inestables (Gutmann, 1999).…”
Section: Discussionunclassified